The Main Ideas of the Economic and Sociological Concept of Emotions by Eva Illouz. Reply to Nina Lyubinarskaya’s Review - Kondrashov, Pyotr (Journal of Economic Sociology, 2023)
This work is a commentary on the review of N. Lyubinarskaya [Lyubinarskaya 2022] on the Russian translation of the book by E. Illouz Why Love Hurts? [Illouz 2020]. In her review, N. Lyubinarskaya highlights important and interesting aspects of the book under review. However, due to the fact that the sociology of emotions is a relatively new discipline, it is likely that most readers are not familiar with other works by Eva Illouz. In this note, we overview the general logic of her concept of the constitutive relationship of capitalism and emotions. According to Illouz, economic systems (or “modes of production”) form cultural and historical matrices (for example, traditional society or capitalism in its various historical forms) that shape models of relations between individuals within social groups , as well as the relationships of individuals to themselves in the sense of self-identification. These social models of relations in the processes of socialization are internalized and become “internal”, “their own” emotional-existential factors of the psyche. Each cultural matrix constitutes its own unique conditions for the realization of feelings and emotional relationships (the ecology of emotions), making the content of emotions specific to a historical and even biographical (the architecture of emotional choice) context. Illouz’s research highlights the radical difference between emotions, particularly love and related positive and negative experiences, between traditional, early capitalist, and modern capitalist societies. She especially reviews the effects of the latter in the context of the sexual revolution of the 1960s and the surge of feminism in the 1970s. She pays special attention to the analysis of the destruction of traditional identification systems as a background to the commodification of emotions (turning them into ‘emodities’). Finally, she discussed that the formation of emotional capitalism in which “positive psychology” establishes a sort of a market dictatorship of happiness (‘happycracy’).